A Convex Model of Equilibrium Growth: Theory and Policy Implications - Jones, Larry E.; Manuelli, Rodolfo (Journal of Political Economy, 1990)
The authors' aim in this paper is to exposit a convex model of equilibrium growth. The model has two features that distinguish it from most other work on the subject: first, the model is convex on the technological side and, second, fixed factors are explicitly included. Existence and characterization results are provided along with some preliminary analyses of taxation and international trade policies. It is shown that the long-run growth rate in per capita consumption depends, in the natural way, on the parameters describing tastes, technology, and policies. It is demonstrated that, in a free-trade equilibrium with taxation, national growth rates of consumption and output need not converge. Copyright 1990 by University of Chicago Press.